Estudos dos mecanismos envolvidos nos efeitos analgésico e anti-inflamatório de dois candidatos a protótipos de fármacos - LQFM 002 e 015 - Lino, Roberta Campos (2011)
The anti-inflammatory drugs available in the market, anti-inflammatory non steroidal and steroidal, are widely used, are effective but are still far from being ideal drugs because they have several side effects (eg. gastrointestinal, renal, etc.). In this paper, two new molecules synthesized by the Laboratory of Medicinal Chemistry Pharmaceutical-UFG LQFM-015 and LQFM-002, are evaluated for their ability antiinflammatory and antinociceptive. Previous studies have shown inhibitory activity on phospholipase A2 of LQFM-015 and LQFM-002. LQFM-015 was synthesized from the metabolite 4-nerolidylcathecol, which also inhibits the enzyme phospholipase A2 (PLA2). In this study, treatment with LQFM-015 (100, 200 and 400 μmol/kg, p.o.) reduced the writhings numbers, but without alters the parameters of open field, rotarod and in the barbituric-induced sleep test. The antinociceptive action was confirmed in the second phase (inflammatory pain) on formalin-induced pain test, whereas the three doses (100, 200 and 400 μmol/kg, p.o.) reduced the time used for reactivity to pain. Treatment with LQFM-015 (100, 200 and 400 μmol/kg, p.o) also reduced edema in rat paw edema model in mice. This anti-inflammatory activity was confirmed by the decreased the cell migration (26%) and the activity of the enzyme myeloperoxidase (56%) with LQFM-015 (155 μmol/kg, p.o.) in the pleurisy model in mice. LQFM-002 is a derivative of pyrazole that in previous studies was capable of reducing PLA2 activity in vitro, reducing cell migration and the concentration of Evans blue in pleural exudate. In this study we evaluated the anti-inflammatory and/or the antinociceptive activity LQFM-002 in vivo. In the model of pain induced by acetic acid treatment (LQFM-002 200 μmol/kg, p.o.) reduced the number of writhing and pain reactivity in the test of pain induced by formalin in the first and second phase. Treatments with LQFM-002 (400 and 800 μmol/kg, p.o.) increased the pain latency in hot plate, also showed changes in the parameters of open field suggestive of an anxiolytic action. In the barbituric-induced sleep LQFM-002 800 μmol/kg, p.o., increased the sleep time is in agreement with an anxiolytic action seen in the open field, but without alters the parameters rota-rod test. Treatment with LQFM-002 reduced the concentration of TNF-α by approximately 25% when compared with vehicle group. The antiinflammatory action of this molecule may be due to reduction of TNF-α. In conclusion LQFM-015 showed anti-inflammatory action that may be related to the reduction of myeloperoxidase activity and LQFM-002 had an anti-inflammatory action possibly due decreased in the levels of TNF-α and analgesic activity involving central mechanisms.